Electrical alternans of the Q-T interval and fatal arrhythmias caused by neonatal cardiac tumor: a case report - Wang, Ge; Ding, Jin; Wu, Hongguang; Chen, Yanhong; Deng, Xiaoqi; Li, Hairui; Li, Haiying (Frontiers in Cardiovascular Medicine, 2025)
Primary cardiac tumors in the fetal and neonatal populations are rare. In neonates, these tumors may present with a range of clinical manifestations, from asymptomatic cases to severe arrhythmias, valvular obstruction, and cardiac dysfunction. This report describes a case of fatal malignant arrhythmia caused by a cardiac tumor in an 8-day-old neonate. The electrocardiogram at birth revealed multiple abnormalities, including ST-T segment alterations, intraventricular conduction block, and bundle branch block. By the sixth postnatal day, the patient developed rapid, polymorphic malignant ventricular arrhythmias. Despite aggressive treatment, the neonate ultimately suffered sudden cardiac death. This case underscores the potentially fatal risk of arrhythmias associated with cardiac tumors.